Surveillance of musculoskeletal injuries and disorders in a diverse cohort of workers at a tertiary care medical center - Pompeii, Lisa A.; Lipscomb, Hester J.; Dement, John M. (American journal of industrial medicine, 2008)
Background The purpose of this study was to investigate the incidence of work‐related musculoskeletal (MSK) injuries and disorders among a dynamic cohort of health care workers, including direct care providers and support services, employed at a tertiary care medical center. Methods Human resources data were used to define the cohort and time at risk. Workers' compensation (WC) records (1997–2003) were utilized to identify work‐related MSK claims. Poisson regression was used to generate gender specific rate ratios and 95% confidence intervals (CI) of MSK injuries among workgroups. Results MSK injuries resulted equally (∼30% each) from lift/push/pull of equipment, patient handling, and slip/trip/falls. Injury rates and their mechanisms varied substantially by occupational group, gender, and race. Even with declining injury rates over time, black workers had rates 2.5 times higher than other workers and women had rates 1.8 times higher than men. Male and female nurses' aides, housekeepers, and radiology technicians had among the highest rates of injury, while lost workdays rates were highest for male and female nurses' aides, female housekeepers, and male patient transporters. Conclusions Differential risk associated with work tasks in highly segregated work populations can contribute to disparities in health, and the patterns we observed partly reflect the high concentration of female and black workers in occupations with increased physical demands. While the greatest public health impact will be achieved by implementing prevention strategies among large workgroups with high injury rates, public health efforts must not ignore smaller, often segregated, workgroups identified in this study as high risk. Am. J. Ind. Med. 51:344–356, 2008. © 2008 Wiley‐Liss, Inc.